Fundamental relation in isolated galaxies, pairs, and triplets in the local Universe - Argudo-Fernández, M.; Duarte Puertas, S.; Verley, S. (Astronomy and astrophysics (Berlin), 2025)
Context. The correlations between star formation rate (SFR), stellar mass (M ⋆ ), and gas-phase metallicity for star-forming (SF) galaxies, known as global scaling relations or fundamental relations, have been studied during the past decades to understand the evolution of galaxies. However, the origin of these correlations and their scatter, which may also be related to their morphology or environment, is still a subject of debate. Aims. In this work, we establish fundamental relations, for the first time, in isolated systems in the local Universe (with 0.005 ≤ z ≤ 0.080), which can give insight into the underlying physics of star formation. We used a sample of isolated galaxies to explore whether star formation is regulated by smooth secular processes. In addition, galaxies in physically bound isolated pairs and isolated triplets may also interact with each other, where interaction itself may enhance or regulate star formation and the distribution of gas and metals within galaxies. Methods. We made use of published emission line flux information from the Sloan Digital Sky Survey (SDSS) to identify SF galaxies in the SDSS-based catalogue of isolated galaxies (SIGs), isolated pairs (SIPs), and isolated triplets (SITs). We also used these data to derive their aperture-corrected SFR (considering two different methods) and oxygen abundance, 12 + log(O/H), using bright line calibrations. Stellar masses for SIG, SIP, and SIT galaxies were estimated by fitting their spectral energy distribution on the five SDSS bands. Results. The SFR results found using both methods seem to be consistent. We compared our results with a sample of SF galaxies in the SDSS. We found that, on average, at a fixed stellar mass, the SIG SF galaxies have lower SFR values than Main Sequence (MS) SF galaxies in the SDSS and central galaxies in the SIP and SIT. On average, SIG galaxies have higher 12 + log(O/H) values than galaxies in the SIP, SIT, and comparison sample. When distinguishing between central and satellite galaxies in the SIP and SIT, centrals and SIG galaxies present similar values (∼8.55), while satellites have values close to M33 (∼8.4). Using the D n (4000) parameter as a proxy of the age of the stellar populations, we found that, on average, SIG and central galaxies have higher D n (4000) values than satellites and comparison galaxies. Conclusions. In general SIG galaxies do not present stellar starbursts produced by interactions with other galaxies, and therefore their gas is consumed more slowly and at a regular pace. On the contrary, SIP and SIT galaxies present higher SFR values at fixed mass (both in central and satellite galaxies). Therefore, the effect of adding one or two companion galaxies is noticeable and produces a similar effect as the typical average environment around galaxies in the local Universe. The successive interactions between the galaxies that form these pairs and triplets enhance the star formation. Based on our results for SIGs, we propose a ground level ‘nurture-free’ SFR–M ⋆ and gas metallicity-SFR–M ⋆ relations for SF galaxies in the local Universe.